2015
DOI: 10.1002/app.42315
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated polyester resins for thermoset applications using renewable isosorbide as a component for property improvement

Abstract: Unsaturated polyester (UPE) resins are used in a variety of thermosetting applications due to the reduced cost when compared to epoxy resins; however, UPE resins also have reduced thermomechanical performance. Investigating avenues to improve the performance of UPEs has led to the use of bio-based starting materials as structural components of the synthesized prepolymers as a result of their advantageous structural features. Isosorbide, a compound derived from renewable feedstocks, has been utilized to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 32 publications
(52 reference statements)
7
53
0
Order By: Relevance
“…Comparing the polyesters with saturated acids, BioUP_1, with SuAc, provides the polyester with higher viscosity, whereas the lowest value was observed for BioUP_3, with SeAc. This result can be explained by the high mobility of the polymeric chains provided by the diacid with longer aliphatic chains [4,5]. For these formulations, similar molecular weights were achieved and, consequently, M n does not have a significant effect on the viscosity of UPs.…”
Section: Results and Discussion 31 Polycondensation Of Ups Based Onmentioning
confidence: 83%
See 4 more Smart Citations
“…Comparing the polyesters with saturated acids, BioUP_1, with SuAc, provides the polyester with higher viscosity, whereas the lowest value was observed for BioUP_3, with SeAc. This result can be explained by the high mobility of the polymeric chains provided by the diacid with longer aliphatic chains [4,5]. For these formulations, similar molecular weights were achieved and, consequently, M n does not have a significant effect on the viscosity of UPs.…”
Section: Results and Discussion 31 Polycondensation Of Ups Based Onmentioning
confidence: 83%
“…It is interesting to note that, despite its low M n , BioUP_6 is the polyester with the highest viscosity. In the case of Iso, it is reported that the oxolane ring has the ability of establishing inter-chain hydrogen bonds, causing additional chain interactions [5] and, consequently, higher viscosities are expected. For the formulations with PDO and BDO (BioUP_4 and BioUP_5, respectively) it was not possible to determine the Gardner viscosity since UPs were immiscible with 2-ethoxyethanol used in the test.…”
Section: Results and Discussion 31 Polycondensation Of Ups Based Onmentioning
confidence: 99%
See 3 more Smart Citations